The relationship between Internet addiction and oral health among high school students in Lattakia - صقور حنين; سميره زريقي (Latakia University Journal -Medical Sciences Series, 2023)
Introduction: In modern society, Internet use has become an indispensable element of everyday life, bringing conveniences from around the world, especially after most of its aspects have become automated, whether for communication, electronic payment, shopping, tourism, transportation, learning..etc, but like other technologies, its use For a long and unconsidered time, had its negative aspects. Study Objectives: This study aimed to assess the oral health status among the group of addicted students, compared with the same age and sex group of the non-addicted. Materials And Methods: the YIAT (Young Internet Addiction Test) was used to collect the sample. we examined, 200 students who were considered addicts, and 200 of non- addicted group between the age of 15-18 years, oral health was assessed by measuring Debris-index-simplified (DIS) values. In addition to a personal questionnaire that included questions about (daily brushing, annual visits to the dentist). Results: The average values of (DIS) for addicts are not significantly higher than for non-addicts. and there is no statistically significant effect of Internet addiction on annual visits to the dentist, or daily brushing. Conclusion: there is no statistically significant effect of Internet addiction on DIS values, annual visits to the dentist and daily brushing.